R-band light-curve properties of Type Ia supernovae from the (intermediate) Palomar Transient Factory. Issue 4 (6th December 2018) - Papadogiannakis, S; Goobar, A; Amanullah, R; Bulla, M; Dhawan, S; Doran, G; Feindt, U; Ferretti, R; Hangard, L; Howell, D A; Johansson, J; Kasliwal, M M; et al.
ABSTRACT: We present the best 265 sampled R-band light curves of spectroscopically identified Type Ia supernovae (SNe) from the Palomar Transient Factory (PTF; 2009-2012) survey and the intermediate Palomar Transient Factory (iPTF; 2013-2017). A model-independent light-curve template is built from our data-set with the purpose to investigate average properties and diversity in our sample. We searched for multiple populations in the light-curve properties using machine learning tools. We also utilized the long history of our light curves, up to 4000 days, to exclude any significant pre- or post- supernova flares. From the shapes of light curves we found the average rise time in the R band to be 16.8^+0.5_-0.6 days. Although PTF/iPTF were single-band surveys, by modelling the residuals of the SNe in the Hubble–Lemaître diagram, we estimate the average colour excess of our sample to be 〈 E ( B − V )〉 ≈ 0.05(2) mag and thus the mean corrected peak brightness to be MR = −19.02 ± 0.02 +5 (H_0 [ km s^-1 Mpc^-1]/70) mag with only weak dependennce on light–curve shape. The intrinsic scatter is found to be σ R = 0.186 ± 0.033 mag for the redshift range 0.05 < z < 0.1, without colour corrections of individual SNe. Our analysis shows that Malmquist bias becomes very significant at z = 0.13. A similar limitation is expected for the ongoing Zwicky Transient Facility (ZTF) survey using the same telescope, but new camera expressly designed for ZTF.